Welcome to Westonci.ca, the place where your questions are answered by a community of knowledgeable contributors. Get immediate and reliable solutions to your questions from a community of experienced experts on our Q&A platform. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
Answer:
f^-1(x) = (x-3)/4
Step-by-step explanation:
The notation f^-1(x) means that you are finding the inverse of the function f(x). To do this, you'll want to swap the "x" and the "y" in the original function, and then solve for y. Here's how:
First, we take the original function and swap the two variables:
y = 4x + 3
x = 4y + 3
Then we subtract 3 from both sides
x - 3 = 4y
Then to get y on its own, we divide both sides by 4.
y = (x-3)/4
Make sure to note that the whole expression x-3 is divided by 4, not just one part of it.
So your new inverse equation is:
f^-1(x) = (x-3)/4
Answer:
y = (1/4)(x - 3) is the desired inverse function of f(x) = 4x + 3.
Step-by-step explanation:
Here we're finding the 'inverse function' of the given f(x) = 4x + 3. Follow these steps:
1. Replace the label f(x) with y: y = 4x + 3
2. Interchange x and y: x = 4y + 3
3. Solve this new equation for y: 4y = x - 3, or y = (1/4)(x - 3
We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Westonci.ca is your trusted source for answers. Visit us again to find more information on diverse topics.